Switching Trains of Thought : The Impact of News Frames on Readers' Cognitive Responses - PRICE, VINCENT and TEWKSBURY, DAVID and POWERS, ELIZABETH (Communication Research, 1997)
This study investigated how journalistic story frames can affect the thoughts and feelings of readers. Two hundred and seventy-eight students participated in two studies, reading and responding to a fictitious story about possible reductions in state funding of their university. Stories were presented in one of four randomly assigned versions, all containing the same information, but varying in their opening and closing paragraphs according to the frame employed: human interest, conflict, or personal consequences. A control version contained the common body only. In Study 1, thoughts listed by participants indicated that the news frames—although they had no influence on the volume of cognitive responses—significantly affected the topical focus and evaluative implications of thoughts generated. In Study 2, evaluations and opinions offered by participants indicated that the news frames also subtly could affect audience decision making about matters of public policy. Implications for shaping public opinion are discussed.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwOTcwMjQwMDUwMDI